Экспериментальные исследования ударных электромеханических преобразователей с использованием пьезо- и тензодатчиков - Болюх, В.Ф.; Щукин, И.С. (Електротехніка і електромеханіка, 2011)
The experimental research method of percussion electromechanical induction type transformers basing on simultaneous measurement of electrical parameters of the inductor and mechanical parameters at action the striker which accelerated by the armature on a struck object has been proposed. The mechanical effect is measured using piezoelectric and strain sensors on two devices when striker moves vertically upwards and downwards. Experiments discovered the features of the transformer associated with the influence of the armature, its form, movement at a prescribed distance, the size of the gap between the inductor and the armature, the parameters of the capacitive energy storage and accelerated load.